A ONE-BILLION-YEAR GAP IN THE PRECAMBRIAN HISTORY OF THE SOUTHERN SIBERIAN CRATON AND THE PROBLEM OF THE TRANSPROTEROZOIC SUPERCONTINENT - Gladkochub D.P.; Donskaya T.V.; Wingate M.T.D.; Mazukabzov A.M.; Pisarevsky S.A.; Sklyarov E.V.; Stanevich A.M. (My University, 2010)
Available geochronological data substantiate the existence of an apparent ca. one billion year gap in geological activity in the southern part of the Siberian craton. The duration of the gap is about 0.8 to 1.1 Ga in the Sayan Uplift and at least 0.9 Ga in the Baikal Uplift. We suggest that the absence of major geological activity in this interval might be due to the southern margin of Siberia occupying an internal position within a Transproterozoic supercontinent, that is, a fragment of Nuna that did not disperse until the late Neoproterozoic breakup of Rodinia. The absence of Mesoproterozoic–early Neoproterozoic sedimentary successions in southern Siberia could possibly be explained by their removal by erosion. Ediacaran subsidence following the breakup of Rodinia may reﬂect the solidiﬁcation of magma chambers that fed Neoproterozoic maﬁc dike swarms. We suggest that a combination of these factors (dike emplacement and erosion) has a signiﬁcant inﬂuence on global tectonics, controlling the uplift and subsidence of ancient cratons.
Keywords: Nuna; Proterozoic; Rodinia; Siberia; supercontinent; tectonics; Докембрий::Протерозой; Precambrian::Proterozoic